Evaluation of the mechanical and release properties of lactose and microcrystalline cellulose and their binary mixtures as directly compressible excipients in paracetamol tablets (2020)
Binary mixtures of microcrystalline cellulose MCC (A), and lactose (L) in ratios at 75:25, 50:50, and 25:75% respectively were prepared. The binary mixtures were subjected to microscopical analysis and density measurements. The mechanical properties of paracetamol tablets formulated with the above excipients were assessed for tensile strength, bonding capacity (using the Ryshkewitch-Duckworth relation) and friability, while drug release properties were assessed for disintegration and dissolution times. The dissolution profiles were fitted into dissolution model equations to determine release mechanism and similarity of release. Microscopic analysis showed that the lactose particles were large, crystalline, and acicular in shape whereas the MCC particles were smaller and irregularly shaped. The binary mixtures had particle shape and sizes in between the parent compounds. The particle size of A25:L75 however, was larger than that of the proprietary brand, Microcelac®. Bulk and tapped densities increased with increasing amounts of MCC in the binary mixtures while particle density had an inverse relationship. Tablets containing A75:L25 had the highest tensile strength and bonding capacity and lowest friability in comparison to other binary mixtures and Microcelac®. However, tablets containing A75:L25 did not show superiority to Microcelac® in terms of paracetamol release. Its release, however, followed the Korsmeyer-Peppas model indicating a super case II transport mechanism. Only comparisons of tablet combinations of Lactose: A25:L75 and MCC: A50:L50 had a similarity factor, f2 >50. Tablets made of A75:L25 exhibited the highest mechanical and release properties of the binary mixtures, as directly compressible excipient in comparison to the parent compounds and Microcelac®. This mixture, A75:L25 therefore, could be developed for commercial use in tablet formulations.